Preformulation Profiling of Capecitabine: Foundation for Novel Oral Anticancer Drug Delivery Systems - Jamdar, Jatin Kumar; Tandekar, Vaishali; Muktamadhavi, Muktamadhavi; Giri, Bhupendra; Prajapati, Vijay Kumar; Kujur, Suchita; Sharma, Harish; Sahu, Gyanesh Kumar (Journal of Neonatal Surgery, 2025)
A crucial stage in creating a stable and efficient pharmaceutical formulation is preformulation studies. The preformulation study on capecitabine, a parenteral antineoplastic medication used to treat colorectal cancers, is the main subject of this work.The physicochemical characterization included solubility, partition coefficient, melting point, ultraviolet-visible spectroscopy, infrared/fourier transform infrared, X-ray diffraction, and high performance liquid chromatography.The findings give critical information for developing a strong and bioavailable formulation that ensures therapeutic efficacy while retaining stability and compatibility. This study serves as a platform for future formulation development and optimization of capecitabine-based medicines.